Modeling the Ukraine Black Sea Economic Region GRP Dependence on Socio-Economic Indicators - Bulgakova, O. (Індуктивне моделювання складних систем, 2013)
This paper presents the results of simulation socio-economic and ecological processes on example of the southern Ukraine under conditions of incomplete information. Construction and implementation of the information technology computer monitoring model of the complex processes state at various levels